Incontinentia Pigmenti in a Newborn. A Case Report - Yahiris García Rodríguez; Grethel Castillo Maspons (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
Incontinentia pigmenti, also known as Bloch-Sulzberger syndrome, is an X-linked dominant neurocutaneous syndrome, which variably affects the tissues derived from the neuroectoderm and mesoderm including the skin, hair, nails, eyes, central nervous system and teeth. Differential diagnoses such as bullous impetigo, bullous pemphigoid, neonatal herpes, cytomegalovirus, mastocytosis and epidermolysis bullosa are considered in the neonatal period. Early diagnosis contributes to the identification of associated conditions that determine the patient's prognosis. Hence, we decided to present this case.